Apurímac: Figures and data for a strategy - Cetraro Cardó, César (2007)
In order to project a regional development policy, up-to-date basic studies are essential that intend to attend to the urgencies of the most excluded population. The author makes a review of the reality of Apurima starting with the geography, the political-administrative division and the demographic process to immediately internalize the living conditions of the population, especially employment, education, infrastructure. The work concludes with a review of the economic activities and the gross domestic product calling especially attention to peasants who currently have just s /. 1.43 a day to sustain himself.